(m^2+2mn+n^2)/4-mn=(m^2-2mn+n^2)/4 你写的貌似错了
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 15:05:25
(m^2+2mn+n^2)/4-mn=(m^2-2mn+n^2)/4你写的貌似错了(m^2+2mn+n^2)/4-mn=(m^2-2mn+n^2)/4你写的貌似错了(m^2+2mn+n^2)/4-mn
(m^2+2mn+n^2)/4-mn=(m^2-2mn+n^2)/4 你写的貌似错了
(m^2+2mn+n^2)/4-mn=(m^2-2mn+n^2)/4 你写的貌似错了
(m^2+2mn+n^2)/4-mn=(m^2-2mn+n^2)/4 你写的貌似错了
(m^2+2mn+n^2)/4-mn=m^2/4+mn/2+n^2/4-mn =m^2/4-mn/2+n^2/4==(m^2-2mn+n^2)/4
已知m+n=-4 mn=2求mn
已知m-n=2,mn=1,求多项式(-2mn+2mn+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=2,mn=1,求多项式(-2mn+2mn+3n)-(3mn+2n-2m)-(m+4n+mn)的值
m-n=7 mn=-5求(3m+5n+4mn)-(2n-4n+6mn)
已知m+n=3,mn=2/3,求mn-mn+mn的值
已知m-n=4,mn=2,求多项式(-2mn+2m+3n)-(3mn+2n-2n)-(m+4n+mn)的值
已 知m-n=4,mn=-1,求:(-2mn+2m+3n)-(3mn+2n-2n)-(m+4n+mn)的值
已知m-n=4,mn=2,求多项式(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
已知m-n=2,mn=1,求多项式(2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
若m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)
若m-n=4,mn=-1求(9-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)
已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=3,mn=-3,求(-m-4n-mn)-(2mn-2m-3n)-(3mn+2n-2m)的值
已知m-n=3,mn=-1,求多项式-2mn+2m+3n-3mn-2n+2m-4n-m-mn的值
若m-n=4,mn=-1,求(-2mn+m+n)-(3mn+5n-5m)-(m+4n-3mn)的值
[(m+n)^2-4mn][(m-n)^2+4mn]+2(mn)^2
急2[mn+(-3m)]-3(2n-mn),m+n=2 mn=-3